White Fulani cattle of West and Central Africa - Tawah, C.L.; Rege, J.E.O. (1996)
The paper reviews information on the White Fulani cattle. Discussions and data on breed origin, classification, distribution, population statistics, ecological settings, utility, husbandry practices, physical characteristics, special genetic characteristics, adaptive attributes and performance characteristics. The breed is economically important for several local communities in many West and central African countries with a substantial population. However, exotic cattle breeds as well as interbreeding with local breeds represent the major threat to the breed. This review identified lack of programmes to develop the breed as being inimical to its long-term existence.